Ambiguity of Adultery Concept (Zina) in Criminal and Justice System (A Comparison between Indonesia, Pakistan, and Turkey) - Agustya Catur Mahendra (Universitas Negeri Semarang, 2019)
Indonesia is a country that has an ideological foundation, namely Pancasila, while Turkey is a country that has a foundation of ideology of Kemalism. Every country must have a different ideological foundation and certainly has a different legal system, as well as the country of Pakistan. In this article, what will be discussed is regarding adultery. Adultery is intercourse between men and women who do not have a legitimate marriage bond according to religion, adultery also can defined sexual relations between men and women who are not bound by marital relations.Â In the book Bidayatul Mujtahid it is stated that adultery is intercourse that occurs not because of a legitimate marriage, not because of false marriage, nor because of ownership (of slaves). Sahal Mahfudz expressed the opinion of the Imams of the School of Understanding adultery with three main points of understanding.Â Such understanding has been agreed upon by the scholars.Â Adultery is the path to damage that can lead to human descent from noble to despicable degrees. In Indonesia, adultery is a crime stipulated in article 284 of the Criminal Code, the article applies if one of the adulterers has been bound to marriage, so for those who are not bound by marriage cannot be criminalized, in article 284 of the Criminal Code as a criminal offense with a prison sentence of up to nine months, with the following conditions; He who is an adulterous wife is being aware that article 27 of the Criminal Code applies to him and married women who commit adultery. In the country of Turkey, adultery is not a criminal act, it is based on secular Turkish ideology and considers that sexual relations are a private area, but adultery can be a cause or an excuse to file a divorce. This makes the perpetrators of adultery who have not or are not bound by marriage do not have any impact or risk of the adultery that they have committed. Whereas in Pakistan, zina acts are adjusted to existing Islamic law.